ANALISIS DAN PERANCANGAN APLIKASI SISTEM INFORMASI AKUNTANSI PERSEDIAAN UNTUK MENINGKATKAN PENGENDALIAN INTERNAL PADA UMKM FILO CR MALANG - Aldo Wicaksono Wibowo; Anik Kusmintarti; Nurafni Eltivia (International Journal of Multidisciplinary Research and Literature, 2022)
This study aims to analyze and design an inventory accounting information system application to improve internal control in MSMEs Filo CR. In addition, add a recording system or feature to help facilitate the raw material inventory control system and internal control. The type of research carried out is applied research using research and development (R&D). where applied research is conducted to apply the findings to solve problems. The research findings contribute to knowledge building in various functional areas of business. In addition, this research aims to develop and provide an output or product that can apply and benefits businesses in the coffee production MSME sector. This research is expected to provide a solution and contribute to the control of coffee raw material inventory by the criteria for the production and quality of accountable and transparent financial reports